2012
DOI: 10.1177/0093854812463349
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Sibling Violence

Abstract: The measurement of violence is a major challenge in aggression research. Because of the heterogeneous nature of violent behavior, problems arise when applying blanket measures to inherently distinct subtypes of aggression. Incidents of intersibling violence (ISV) exacerbate these problems because siblinghood represents a unique offender–victim situation. This research explored whether an existing two-factor model for severe violence found in a sample of 250 adult offenders (age M = 26.8, SD = 5.9) could be gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 62 publications
(117 reference statements)
2
13
0
Order By: Relevance
“…The present study extended prior research findings (Ibabe, Arnoso, & Elgorriaga, 2014;Khan & Cooke, 2013) by examining aggression perpetrated by two mental health samples and the use of weapons. Prior research that had examined family aggression among juvenile offenders found that the majority of the sample had used a weapon (i.e., heavy or sharp objects) to perpetrate aggression (Khan & Cooke, 2013), while research that examined clinic-referred youth found no weapon use (Nock & Kazdin, 2002).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The present study extended prior research findings (Ibabe, Arnoso, & Elgorriaga, 2014;Khan & Cooke, 2013) by examining aggression perpetrated by two mental health samples and the use of weapons. Prior research that had examined family aggression among juvenile offenders found that the majority of the sample had used a weapon (i.e., heavy or sharp objects) to perpetrate aggression (Khan & Cooke, 2013), while research that examined clinic-referred youth found no weapon use (Nock & Kazdin, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…Recently, perpetration of aggression toward family members by young people has been the focus of research which seeks to understand inter-sibling aggression (Khan & Cooke, 2013) and aggression toward parents (Ibabe, Jaurequizar, & Diaz, 2009). Based on prevalence data, sibling aggression is the most common form of aggression at home (Eriksen & Jensen, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of differing terminology, such as aggression, violence, abuse, bullying, or rivalry, to describe aggressive sibling interactions illustrates the lack of agreement between researchers (Eriksen & Jensen, 2009;Krienert & Walsh, 2011). Furthermore, there are ongoing debates concerning key definitional and operational features, such as the need to incorporate concepts of intent or repetition into the definition (Khan & Cooke, 2013), and whether behavior should be categorized according to severity to distinguish between mild and more severe forms of sibling aggression (Eriksen & Jensen, 2009;Khan & Cooke, 2013). These issues are still some way from being resolved, and at present there appears to be no standard definition or means of measuring aggression between siblings; therefore studies differ notably in the types of behavior they consider to constitute sibling aggression.…”
Section: Definition and Prevalencementioning
confidence: 99%
“…In comparison to the study of peer aggression, sibling aggression has received less research attention (Eriksen & Jensen, 2009;Skinner & Kowalski, 2013); however, recently there appears to be a renewed interest in the subject, marked by attempts to more clearly define and document the extent of aggression among siblings (e.g. Khan & Cooke, 2013;Wolke & Skew, 2012).…”
Section: Introductionmentioning
confidence: 99%